Managerial career development for women in health contexts : metamorphosis from quandary to confidence. - Ross, Frances M. (Curtin University, 1997)
The aim of this study was to construct a theory for women's managerial career development that explained how women in health care services and health science faculties achieved senior management positions and developed their careers. It sought to discover the main barriers to career progress and achievement of senior level positions by women in health related organisations and to identify how women managers dealt with obstacles. In-depth interviews with 35 women managers in senior positions in 19 different organisations from three different cultural regions formed the major data source; observations, field notes, personal and operational journals, documents, and literature supplemented this data.This research was conducted in two phases. In phase one a descriptive approach was used to develop propositions about women managers and their careers. These propositions formed the guidelines for phase two. The second phase used grounded theory methods, incorporating feminist and interpretative perspectives to identify the previously inarticulated core problem shared by participants. The barriers that women encountered were the contradictory, inconsistent and incompatible assumptions about their potential to have long term careers and ability to move into senior level management positions.These assumptions had been received during their life and educational experiences, as well as from their organisations. The gendered context of health care organisations and university educational institutions contributed to the limited career aspirations and career progress of women with health professional qualifications. By applying grounded theory strategies for analysis of the data, it was discovered that the women managers dealt with this problem through a core process, labelled metamorphosis, a four stage process for overcoming assumptions. This core variable was the way these women managers moved from managing without confidence to managing with confidence and assurance.This process occurred over time having four stages, each involving different activities and strategies. The progressive spiral stages were: being in a quandary (struggling with incompatible and contradictory assumptions); observing, examining and reflecting (on the impact of internal and external assumptions on their behaviour in organisational contexts, then realising that opportunities existed); learning and reframing (the managerial skills in order to re-frame their assumptions about the traditional characteristics of a manager); and finally change and transformation into being confident managers, so developing women's presence in management.The findings generated a theory which proposed a managerial career development model for enabling women to manage with confidence and assurance. The outcome was a theoretical model which recognised the dynamic interaction between contexts (professional, organisational, political, economic, cultural, and research); a picture of women managers (personal beliefs, skills, characteristics, attributes of life long learning, relationship between life and career roles, and ways of changing contexts); and the inner energy force creating women's presence in health related organisations (core process and power of their metamorphosis).Contributing to the development of this theory of metamorphosis was the recognition that being and doing research with women involved valuing the personal learning process. This thread has been integrated into the research fabric to strengthen the reflective and personal experiences of research. Using and valuing women's stories enabled their voices and visibility to be taken out of the shadows and demonstrated that they can be pioneers in their own lives. The sense of collaboration in research, education, and community healing will gain from encouraging women to aspire to leadership and management positions.